2006
DOI: 10.1128/aem.00756-06
|View full text |Cite
|
Sign up to set email alerts
|

Granadaene: Proposed Structure of the Group B Streptococcus Polyenic Pigment

Abstract: The goal of this work was to determine the chemical nature of the red pigment produced by Streptococcus agalactiae, which has been thought to be a carotene. We extracted the pigment with 0.1 M KOH and purified it by column chromatography on Sephadex LH. Data from elemental analysis and mass and nuclear magnetic resonance spectra lead us to propose the structure to be that of a new ornithine rhamno-polyene with 12 conjugated double bonds, to which we have assigned the trivial name granadaene.Streptococcus agala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
65
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 16 publications
(9 reference statements)
5
65
2
Order By: Relevance
“…Based on the proposed synthesis pathway (9,11), this might suggest that the presence of ornithine is essential for both pigmentation and hemolytic activity, whereas the absence of rhamnose mostly affects hemolysis. Further chemical analysis would greatly improve our understanding of the structure-function of this rhamnolipid toxin (9,11,20), which is unrelated to the known Gram-positive poreforming toxins (45)(46)(47)(48). Lastly, we confirmed that the ABC transporter encoded by cylAB is critical for hemolysis and pigmentation (22).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Based on the proposed synthesis pathway (9,11), this might suggest that the presence of ornithine is essential for both pigmentation and hemolytic activity, whereas the absence of rhamnose mostly affects hemolysis. Further chemical analysis would greatly improve our understanding of the structure-function of this rhamnolipid toxin (9,11,20), which is unrelated to the known Gram-positive poreforming toxins (45)(46)(47)(48). Lastly, we confirmed that the ABC transporter encoded by cylAB is critical for hemolysis and pigmentation (22).…”
Section: Discussionsupporting
confidence: 52%
“…However, it was recently established that the ␤-h/c and the pigment correspond to a unique molecule called granadaene (9,11), a 676-Da ornithine rhamno-polyene (11,20). Granadaene may be entirely synthesized by the 12 genes of the cyl operon (11,19,21).…”
mentioning
confidence: 99%
“…The level of betahemolytic activity correlates with the amount of the red pigment produced by the organism (7,26,29). Recently, the structure of the pigment was determined (26). It was shown to be an ornithine rhamno-polyene with a linear chain of 12 conjugated double bonds and was assigned the trivial name granadaene.…”
mentioning
confidence: 99%
“…The level of betahemolytic activity correlates with the amount of the red pigment produced by the organism (7,26,29). Recently, the structure of the pigment was determined (26).…”
mentioning
confidence: 99%
“…The GBS pigment has been recently identified as a glycopolyene (14). The detection of orange-red pigmented colonies in Granada medium is an easy way to screen and identify GBS in clinical laboratories (13).…”
mentioning
confidence: 99%